Creativity visualization identity: "Orang Asli dais decoration" craft exposure development / Muhamad Hafiz Hassan, Muhammad Ashraf Halidi and Muhammad Fakhruddin Ahmad - Hassan, Muhamad Hafiz; Halidi, Muhammad Ashraf; Ahmad, Muhammad Fakhruddin (2023)
Visual Communication is an exposure to human beings since time immemorial by a multicultural society. Orang Asli have been exposed to visual communication in the production of traditional crafts throughout their ancestors. It is developed informally among them especially in the production of decorations for events such as weddings. The objective of this study is to explore the process of visual documentation of dais decoration Orang Asli community that can be analysed to reveal whose identity has an influence on today's society. This study aims to explain the development of Orang Asli exposure through identity visualization using the art of decorative production and being recognized by outsiders. The research area was located at Kampung Orang Asli Batu 12, Gombak, Selangor to get visual data collection. Several research methods have been implemented such as focus group interviews with selected Orang Asli traditional craft operators, literature review and observations in the field documented using written notes, photographs, audio interviews. Several data have been collected extracting Erwin Panofsky's Theory of Iconography is used to analyse and extract the three main elements that describe aesthetics, usability and technical.